Mechanisms of Landslide Destabilization Induced by Glacier‐Retreat on Tungnakvíslarjökull Area, Iceland. Issue 14 (21st July 2022) - Lacroix, Pascal; Belart, Joaquin M. C.; Berthier, Etienne; Sæmundsson, Þorsteinn; Jónsdóttir, Kristín
Abstract: The massive worldwide deglaciation leads to more frequent slope instabilities in mountainous terrains. The physical processes leading to such destabilizations are poorly constrained due to little monitoring of dynamic parameters at the local scale. Here we study a very large slow‐moving landslide (∼0.8 km 2 ), on the flank of Tungnakvíslarjökull glacier in Iceland. Based on a combination of remote sensing images, we monitor the landslide and glacier kinematics over 75 years, with a focus over the period 1999–2019 when rapid glacier wastage has been observed. The landslide accelerates from 2 to 45 m/yr in the 6 years following a sudden increase in glacier mass loss. This acceleration coincides with intense quake activity (M ℓ < 2.8), recorded by a regional seismic network. We show that this seismicity is caused by the landslide sliding on a rough surface. The evolution of the quake magnitudes suggests a progressive segmentation of the landslide mass during its acceleration. Plain Language Summary: Glacier‐retreat may lead to a destabilization of adjacent slopes that can evolve into large landslides. The time‐scales, as well as the controlling factors of the landslide response to this glacier retreat are poorly known, due to few observations of landslide dynamics in the vicinity of glaciers over the long term. To fill this gap, we document the dynamics of a large landslide in Iceland, developing on the flank of Tungnakvíslarjökull glacier, that underwent strong retreat after 1994. Based on aerial images since 1945 and satellite images since 1987, we calculate the motion of the landslide through time. We show that the landslide accelerated from 2 to 45 m/yr in the 6 years following the onset of glacier retreat. This acceleration coincides with earthquakes of small magnitudes (M ℓ < 2.8), produced by the landslide motion. Their analysis suggests that the landslide mass is progressively fragmented during the acceleration. This study opens interesting perspectives for landslide studies by combining seismic records from regional networks and 3D motions from satellites. Key Points: We monitor the dynamics of a very large slow‐moving landslide over 75 years, developing on the flank of a glaciated valley The landslide kinematics is strongly controlled by the glacier retreat, and produce seismicity correlated with the landslide velocity The acceleration is linked with progressive segmentation of the landslide mass